2009
DOI: 10.1039/b910053a
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte analysis and differentiation using high speed microfluidic single cell impedance cytometry

Abstract: Miniature high speed label-free cell analysis systems have yet to be developed, but have the potential to deliver fast, inexpensive and simple full blood cell analysis systems that could be used routinely in clinical practice. We demonstrate a microfluidic single cell impedance cytometer that performs a white blood cell differential count. The device consists of a microfluidic chip with micro-electrodes that measure the impedance of single cells at two frequencies. Human blood, treated with saponin/formic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
374
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(389 citation statements)
references
References 17 publications
10
374
0
Order By: Relevance
“…Conceptually, this approach represents a downscaling of the classical metabolomics approach. The complete setup has not yet been realized, but many different units required for the microfluidic chip have been developed separately, such as lysis (see, for example, [32]), impedance-based cell size measurement [33], CE separation (e.g. [34]).…”
Section: Ms-based Approaches For Single Cell Metabolomicsmentioning
confidence: 99%
“…Conceptually, this approach represents a downscaling of the classical metabolomics approach. The complete setup has not yet been realized, but many different units required for the microfluidic chip have been developed separately, such as lysis (see, for example, [32]), impedance-based cell size measurement [33], CE separation (e.g. [34]).…”
Section: Ms-based Approaches For Single Cell Metabolomicsmentioning
confidence: 99%
“…The corresponding values of S x and S y were calculated by extracting their magnitude with respect to the current signal baseline (I 0,x and I 0,y ). The anisotropy index was calculated as: AI = (S x /S y ) at (x,y)=0 (7) Results and discussion…”
Section: Discussionmentioning
confidence: 99%
“…In addition to WBC count, microfluidic flow cytometry has also been used for analyzing a variety of particles. [126][127][128][129][130] An impedance flow cytometry design using coplanar electrodes was demonstrated by Gawad et al 126 As shown in Fig. 4(a), three microfabricated electrodes were integrated on the bottom of the microfluidic channel.…”
Section: Impedance Flow Cytometry (Ifc)mentioning
confidence: 99%
“…129 This device design enabled direct correlation of impedance signals from individual cells with their biochemical phenotypes. A 3-part WBC differential count of human blood was well achieved.…”
Section: Impedance Flow Cytometry (Ifc)mentioning
confidence: 99%